Developments in the Collision and Grounding of Ships and Offshore Structures : Proceedings of the 8th International Conference on Collision and Grounding of Ships and Offshore Structures (ICCGS 2019), 21-23 October, 2019, Lisbon, Portugal /: Proceedings of the 8th International Conference on Collision and Grounding of Ships and Offshore Structures (ICCGS 2019), 21-23 October, 2019, Lisbon, Portugal. (2019) - Unknown
No abstract available